If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + -1(4m + -50) = 32 Reorder the terms: 15 + -1(-50 + 4m) = 32 15 + (-50 * -1 + 4m * -1) = 32 15 + (50 + -4m) = 32 Combine like terms: 15 + 50 = 65 65 + -4m = 32 Solving 65 + -4m = 32 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-65' to each side of the equation. 65 + -65 + -4m = 32 + -65 Combine like terms: 65 + -65 = 0 0 + -4m = 32 + -65 -4m = 32 + -65 Combine like terms: 32 + -65 = -33 -4m = -33 Divide each side by '-4'. m = 8.25 Simplifying m = 8.25
| 8+4m=9m-7 | | 3a+2b=c | | i=prt | | ab+c=d | | -5n-8+56n=-8 | | .22y-.8=.12y+1-.8y | | 7+2(4-x)=7-2(x-4) | | 11(r)=10 | | 2t+8-t=-3 | | 11b+12c+3b-2c= | | 8c+5=4c-11 | | 3x+2=5x-8 | | 3t-25=3+7t | | 11+12c+3b-2c= | | 13+2(3x+1)=9x+12 | | 3p+12-5p=22 | | -3n=18-6n | | 3x-4=2x+6 | | 1-3y+y=5 | | -3(n+4)=6(1-h) | | 5(x+1)-4=x-5 | | 8x-18=3x+12 | | -2+-2(x-3)=8 | | 18.9=2.1x | | 2(3x-24)-(5x+9)=4x-12 | | 4(x-3)+3x=16 | | -6n-20=-20n+4-12n | | 5x+1=x | | 3x-4=2x-6 | | 6.2=3x+4-2X | | 4x=2+4 | | 6x+14=20+4x |